Tesla Design in Solar Roof Top - Nakkeeran, S. (International Journal of Psychosocial Rehabilitation, 2019)
Rooftop solar power systems are picking up a second job on the distribution grids that deliver electricity to homes and businesses. Right now, their photovoltaic panels just generate electricity but within a few months some systems will also start moonlighting as junior grid regulators-a role that could keep them busy even after the sun goes down